Cross-Layer QoS Optimization of Wireless Sensor Network for Smart Grid - Wei Sun; Jianping Wang (International Journal of Distributed Sensor Networks, 2014)
Wireless Sensor Network (WSN) has been considered as a promising solution for Smart Grid due to the significant advantages over traditional communication technologies. However, as a necessary function for monitoring, diagnosing, and controlling of remote electrical equipment, Quality of Service (QoS) is still a challenging problem in applying WSN in Smart Grid. This paper presents a comprehensive experimental study on optimization of multiobject QoS in cross-layers of WSN protocol. In PHY layer, a Link Quality Estimator is studied for the purpose of evaluating link quality under harsh Smart Grid environments. In MAC layer, a QoS Enhanced MAC algorithm is used to prevent disorderly contentions among nodes and to allocate more channel resources for critical traffic; in NWK layer, a routing algorithm is introduced for multiobject QoS optimization. All the algorithms are cooperated with each other in cross-layer manner to improve end-to-end reliability and latency. In comparison with other counterparts, the proposed algorithms achieve preferable performances. Finally, field experiments were conducted, the result of which showed that the proposed algorithms outperform the ZigBee protocol and the original Distribution Grid wireless communication technology in terms of the QoS performance of critical traffic.